Cyclophilin Inhibitor NV556 Reduces Fibrosis and Hepatocellular Carcinoma Development in Mice With Non-Alcoholic Steatohepatitis - Kuo, Joseph; Serrano, Sonia Simón; Grönberg, Alvar; Massoumi, Ramin; Hansson, Magnus Joakim; Gallay, Philippe (Frontiers in Pharmacology, 2019)
Hepatocellular carcinoma (HCC), the third major cause of cancer mortality, can result from non-alcoholic steatohepatitis (NASH). Due to limited efficacy of drugs approved for HCC and no drug available yet for NASH, identification of new effective treatments is crucial. Here, we investigated whether NV556, a cyclophilin inhibitor derived by sanglifehrins, would NV556 decreases the development of NASH and HCC in a preclinical mouse model. For our experiment, male mice were administered streptozotocin to disrupt pancreatic cells and nourished with high-fat diet since 3-weeks-old. of age. Afterward, NV556 or vehicle was orally administered daily for 6 weeks before the 14-week-old time point for the development of NASH, or 10 weeks before the 30-week-old time point for the establishment of HCC. Body weight, blood glucose level, and liver weight were recorded. Moreover, for NASH, livers were histologically examined for inflammation and steatosis. Collagen was measured by Sirius Red staining of hepatic tissues. Systemic cytokine levels in serum were detected by multiplex assays. For HCC, nodules of livers were measured, and scored according to a developed system with number and size of nodules as criteria. NV556 significantly decreased collagen formation deposition (p=0.0281), but did not alter inflammation, steatosis, body and liver weight, and systemic cytokine production compared to control mice with NASH symptoms. For HCC, NV556 statistically reduced the number (p=0.0091) and diameter of tumorous nodules (p=0.0264), along with liver weight (p=0.0026) of mice. Conclusions: Our study suggests NV556 as a promising candidate for treatment of NASH-derived fibrosis and HCC.